Intensity of side effects of topical glaucoma medication and its influence on adherence behavior in patients with glaucoma - Yu, Alice L.; Weise, Stefanie; Welge-Lüssen, Ulrich-Christoph (Clinical Ophthalmology, 2014)
The aim of this study was to investigate the intensity of side effects that patients attribute to their topical glaucoma medication and their relationship to adherence behavior.This was a questionnaire-based study of 123 glaucoma patients at a university eye clinic in Erlangen, Germany. An initial questionnaire asked about patient demographic data, the treatment plan, and intensity of side effects, and included Adherence to Refills and Medication Scale 2 (ARMS2) and visual analog scale (VAS-AD) scores. In a follow-up questionnaire, the treatment plan, intensity of side effects, ARMS2, and VAS-AD were reanalyzed.Most patients reported having few side effects, although only 20% said that they had no symptoms suggestive of side effects at all. The patients showed good adherence behavior on both the ARMS2 and VAS-AD scores, which were stable over time. The intensity of side effects experienced in the previous 7 days did not correlate with adherence scores and had no predictive value for adherence.This study could not detect any significant influence of the subjectively experienced intensity of side effects on patients' adherence behavior. However, we believe that a simple and clear treatment plan with few side effects is still preferred by most patients.
EVALuna2:21198